Delignification of Date Palm Fronds using Modified Organosolv Technique - Mahdi, Yasmeen Salih; Mohammed, Asem Hassan; Mohammed, Alaa Kareem (Al-Khwarizmi Engineering Journal, 2017)
Abstract   In this study, modified organic solvent (organosolv) method was applied to remove high lignin content in the date palm fronds (type Al-Zahdi) which was taken from the Iraqi gardens. In modified organosolv, lignocellulosic material is fractionated into its constituents (lignin, cellulose and hemicellulose). In this process, solvent (organic)-water is brought into contact with the lignocellulosic biomass at high temperature, using stainless steel reactor (digester). Therefor; most of hemicellulose will remove from the biomass, while the solid residue (mainly cellulose) can be used in various industrial fields. Three variables were studied in this process: temperature, ratio of ethanol to water and digestion time. Statistical experimental design type Central Composite Design (CCD) has been used to find a mathematical relationship between the variables and the remaining lignin percent as dependent variable. The results obtained in this study were represented by a polynomial mathematical equation of the second degree.  The results showed that the best digestion time was (80 minutes), which gave the best percent remaining concentration of lignin (3%) at temperature of 185oC and ratio of ethanol: water equal to 50: 50 wt/wt. In order to reduce digesting time, the effect of using different catalysts have been studied such as (NaOH, H2SO4, Ca (OH) 2) at low concentration (0.025, 0.025, 0.05M) respectively. It was found that the best catalyst is sodium hydroxide at concentration (0.025) mol/L which gave the same percent of  lignin 3% but with low digestion time about 30 min.Keywords: Biomass pre-treatment, delignification, lignin, organosolv, date palm fronds.